STRATEGIC MANAGEMENT IN A NATIONAL OIL CORPORATION: THE CASE OF LIBYA - Analoui, Farhad; Atamna, Abdallah Enbaia; Analoui, Bejan David (European Scientific Journal, ESJ, 2015)
This empirical study investigated senior managers’ perceptions and application of strategic management in the Libyan National Oil Corporation (NOC). Key factors influencing the processes of strategic management were identified and overall findings have been compared with a model of strategic management. A case study approach was adopted, based on a two-stage research design. The first stage comprised of a survey involving seventy senior managers and was followed by twelve semi-structured interviews to deepen the questionnaire findings with qualitative data. Findings suggest that the Libyan NOC may have relied too heavily in the past on strategy formulation and strategic management as the preserve of a very few individuals at the top of the organization. Whilst political directives set the strategy for the whole organisation, a gap in knowledge and understanding existed between the senior business managers and the political appointments to the Board. The case study does not necessarily reflect the situation in other NOCs. Furthermore, it excludes the impact of the revolution in Libya. Recommendations have been made for improving practice concerned steps in the strategic management process and senior managers’ effectiveness within the Board team. In the context of an example of a state-owned enterprise, the inclusion of three elements was suggested: Board effectiveness, medium-term objectives and social responsibility as an aspect of environmental scanning. This is a first time empirical study of senior managers’ perceptions of strategic management in a National Oil Company.